Write choices elements of nonfiction storytelling - Hertz, Sue (SAGE/CQ Press, 2016)
Developing narrative nonfiction writers at any stage of their career Write Choices: Elements of Nonfiction Storytelling helps writers cultivate their nonfiction storytelling skills by exploring the universal decisions writers confront when crafting factual narratives. Rather than isolating various forms of narrative nonfiction into categories or genres, Sue Hertz focuses on examining the common choices all true storytellers encounter, whether they are writing memoir, literary journalism, personal essays, or travel stories. Write Choices also includes digital storytelling. No longer confined to paper, today's narrative nonfiction writers must learn to write for electronic media, which may also demand photos, videos, and/or audio. Integrating not only her own insights and experience as a journalist, nonfiction book author, and writing instructor, but also those of other established nonfiction storytellers, ..